Concomitant Lung Cancer and Gastrointestinal Stromal Tumor: First Report of Hypoxia Imaging With 18F-FAZA PET/CT. (July 2017) - Mapelli, Paola; Incerti, Elena; Fallanca, Federico; Bettinardi, Valentino; Compierchio, Antonia; Masiello, Valeria; Doglioni, Claudio; Rossetti, Francesca; Negri, Giampiero; Gianolli, Luigi; Picchio, Maria
Abstract : Abstract: A 76-year-old man underwent 18 F-FDG PET/CT to complete staging and characterize a suspicious lung mass. Images showed intense uptake in the lung lesion and faint uptake in correspondence of a gastric mass, which was subsequently biopsied revealing a gastrointestinal stromal tumor. A 18 F-FAZA PET/CT was also performed because of patient's enrollment in a prospective clinical trial (trial registration no. EudraCT 2011-002647-98), showing heterogeneous uptake of 18 F-FAZA in the pulmonary lesion and faint uptake in correspondence of the gastrointestinal stromal tumor.